ELECTRIC VEHICLES IN SERBIA: INSTRUMENT FOR THE ENERGY TRANSITION? - Kuzman, Milos (Pravni zapisi, 2023)
The increasing global impact of climate change has not circumvented Serbia. Committed to take measures that will reduce the impact of climate change through numerous international conventions, the Republic of Serbia has started implementing the energy transition as one of the instruments with which it aims to achieve the set goals. Electric and hybrid vehicles represent one of the ways that the energy transition can be accelerated; the initial provisions on them found their place in positive law in April 2021. This paper will discuss whether the adopted regulations in this area represent a good starting point for achieving the goals of the energy transition, as well as what further measures need to be implemented in order to achieve the desired effect.